2019
DOI: 10.1177/0972150919859101
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Employee Well-being: Development and Validation of a Scale

Abstract: Employee well-being is always found to be strategically relevant to organizations and individuals and has developed into one of the focal areas of research in the study of organizations. However, researchers have shown lots of interest in this field due to the lack of a proper theoretical model and comprehensive scientific tools to measure employee well-being at work. The present study aims at developing and validating a multidimensional scale of employee well-being through exploratory and confirmatory factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 65 publications
2
75
0
7
Order By: Relevance
“…Then a correlation and regression analysis were conducted to test the research hypotheses. It can be concluded that employees' perception of remote working positively affects employees' psychological wellbeing (β=0.497, ≤0.05), which means that respondents feel a high sense of accomplishment and good psychological health while working remotely, which contradicts the findings of Pradhan and Hati (2019); Prasad et al (2020), who explained that psychological wellbeing is negatively affected due to the absence of social exchange and feeling of isolation that remote workers usually experience. Consequently, Hypothesis 1 is not supported.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Then a correlation and regression analysis were conducted to test the research hypotheses. It can be concluded that employees' perception of remote working positively affects employees' psychological wellbeing (β=0.497, ≤0.05), which means that respondents feel a high sense of accomplishment and good psychological health while working remotely, which contradicts the findings of Pradhan and Hati (2019); Prasad et al (2020), who explained that psychological wellbeing is negatively affected due to the absence of social exchange and feeling of isolation that remote workers usually experience. Consequently, Hypothesis 1 is not supported.…”
Section: Discussionmentioning
confidence: 89%
“…But now, with the new working norm (working from home policy), lines between personal and work life will blur even for professionals that are used to working from home as an increasing number of schools close, meaning children will be at home and working parents might struggle to separate responsibilities, which might affect the worker's overall wellbeing (Staglin, 2020). Hence, Pradhan and Hati (2019) defined employee wellbeing as the quality of work-life; it is the employee's wellbeing that is affected by workplace interventions; it is all about the psychological, physical, and emotional health of employees (Juniper, Bellamy & White, 2011). WHO (2020) provided a comprehensive definition for employee well-being and described it as a state of every individual employee to understand his capability, manage the normal stresses of life, work productively, and contribute to her/his community.…”
Section: Remote Working and Employee Wellbeingmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of wellbeing is used differently, sometimes broadly involving health and stress and sometimes specific and then often limited to positive and/or negative effect. One large instrument of employee well-being developed by Pradhan and Hati, (2019) is formed by four discreet factors: social well-being, psychological well-being, subjective well-being and workplace well-being. The present study made use of workplace wellbeing instrument similar to the mental health continuum developed by Corey Keyes (Keyes, 2002;Reinhardt, Horváth, Morgan, & Kökönyei, 2020) that is built upon emotional wellbeing, psychological wellbeing and social wellbeing.…”
Section: Workplace Wellbeingmentioning
confidence: 99%